2021
DOI: 10.1002/clc.23572
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac amyloidosis‐A review of current literature for the practicing physician

Abstract: The amyloidoses are a family of diseases in which misfolded precursor proteins aggregate to form amyloid and deposit in body tissues. A very serious yet underrecognized form of this disease is cardiac amyloidosis, in which amyloid deposits into the extracellular space of the myocardium, resulting in thickening and stiffening of ventricular walls with resultant heart failure and conductive dysfunction. This review provides a discussion of the pathogenesis and clinical presentation of cardiac amyloidosis subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 38 publications
1
60
0
6
Order By: Relevance
“…Moreover, global pattern of LGE is also shown to provide incremental prognostics over biomarker stage [ 17 ]. Finally, cMRI is useful in recognizing concentric and symmetric LV thickening which tends to be far more frequent in AL amyloidosis then in ATTR amyloidosis (68% vs. 18%) [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, global pattern of LGE is also shown to provide incremental prognostics over biomarker stage [ 17 ]. Finally, cMRI is useful in recognizing concentric and symmetric LV thickening which tends to be far more frequent in AL amyloidosis then in ATTR amyloidosis (68% vs. 18%) [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, global pattern of LGE is also shown to provide incremental prognostics over biomarker stage [17]. Finally, cMRI is useful in recognizing concentric and symmetric LV thickening which tends to be far more frequent in AL amyloidosis then in ATTR amyloidosis (68% vs. 18%) [18,19]. The voltage along the short axis of the heart is diminished by the phenomenon of voltage cancellation (yellow dotted arrows), while the voltage along the QRS axis in the horizontal plane (yellow solid arrow, Figure 4B), and long axis of the ventricle, such as the voltage in lead V3 used for calculation of Cornell criteria for LVH, is less affected by this phenomenon of cancellation (no opposing walls along this axis).…”
Section: Qrs Voltagementioning
confidence: 99%
“…Cardiac amyloidosis is currently considered an underestimated cause of heart failure 1,2 . Recent studies reported that high prevalence of microvascular dysfunction in cardiac amyloidosis is one of pathophysiological mechanisms of heart failure in cardiac amyloidosis 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac amyloidosis is currently considered an underestimated cause of heart failure. 1 , 2 Recent studies reported that high prevalence of microvascular dysfunction in cardiac amyloidosis is one of pathophysiological mechanisms of heart failure in cardiac amyloidosis. 3 , 4 , 5 Amyloid deposition in the vessel walls and extrinsic compression from perivascular and interstitial amyloid infiltration have impact on microvascular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Amyloidosis is a disease entity in which proteins of abnormal structure gather in tissues [1]. The biochemical classification of amyloidosis includes the division into three, most common types: amyloidosis AL (Light chain), amyloidosis AA (Amyloid A) and amyloidosis ATTR (Transthyretin) [2].…”
Section: Introductionmentioning
confidence: 99%